Penyelesaian Sengketa dalam Praktik Ekonomi Syariah di Luar Pengadilan menurut Hukum Islam - Darwinsyah Minin (Universitas Syiah Kuala, 2011)
ABSTRACT: The exixting of Islamic law regulations are the rule regulated in the sharia law and a small number are found in the decision of the National Sharia Board and in the Indonesia Bank Regulation. In terms of settling the dispute between Islamic bank and its problem, the board applies two different approaches; namely the decision of the board and the Indonesian Civil Law. Therefore, this paper explores the dispute in the Islamic economic law outside the court in accordance to sharia law. The method applied is analysis content from the relevant sources. The non-litigation dispute settlement ruled in the holy book of Quran are very that can be applied in solving the disputes of economy and finance. A part from Quran and the saying the prophet, there are some sources such as Sunan al Daruquthni, Ibnu Khuzaimah Musnad Abu Ya’la al Musili, Musnad Abu, Awanah, Musnad Abu Daud al Yayalisi, Musnad al Bazzar, etc which are the sources of Islamic law that can be applied in solving the disputes. The Non Litigation Settlement of Islamic Economy Practice Dispute Based on Islamic Law